3D Printing and Rapid Replication of Advanced Numerically Generated Rough Surface Topographies in Numerous Polymers. Issue 1 (9th September 2022) - Perris, Jack; Kumar, Charchit; Xu, Yang; Tassieri, Manlio; Kartal, Mehmet E.; Gadegaard, Nikolaj; Mulvihill, Daniel M.
Abstract : An approach to rapidly produce high‐quality polymer surface topographies from numerically generated surfaces is presented. The approach uses an advanced surface generation tool to flexibly design surfaces with user‐defined topography characteristics over a large range of surface roughness. Roughness instances with root mean square roughness 25, 50, and 100 μm are studied. 3D printing is used to create a master surface and polymer casting and injection molding are employed to enable rapid replication in various polymers. The cross‐correlation ratio (CCR) and a mean difference approach were used to assess replication quality. Injection molding provides high throughput with high replication quality up to CCR ≈ 0.74. While casting in low‐viscosity polymer resins enables slightly improved high‐quality replication (CCR up to ≈0.82) with reduced throughput. Key results include the ability of the 3D‐printed surfaces to replicate tailored variations in surface topography (e.g., amplitude and frequency) and the importance of low viscosity resins in maximizing replication quality in polymer casting. Several interfacial and surface phenomena (both mechanical and biological) are sensitive to surface roughness. The main application lies in providing a valuable tool for research looking at topography influencing phenomena ranging from friction and lubrication to aerodynamic drag, algae growth, and cell growth. Abstract : An approach to rapidly produce high‐quality polymer surface topographies from numerically generated surfaces is presented. An advanced surface generation tool is used to flexibly design surfaces with user‐defined topography over a large range of surface roughness. 3D printing is used to create a master surface, and polymer casting and injection molding are employed to enable rapid replication in various polymers.